Study of Aluminum Foam Sandwiched Bonnet Based on Pedestrian Protection and Orthogonal Design - Yang, Na; Zhao, Guifan; Li, Congsheng; Li, Hua; Wang, Jianfeng (Asian Journal of Chemistry, 2014)
In order to reduce head injuries during vehicle-to-pedestrian impacts, the aluminum foam sandwiched (AFS) bonnet was designed and analyzed. Firstly, the finite element models of the pedestrian-engine bonnet were established according to the statutes of the EEVC WG17. The acceleration curve and head injury criterion (HIC) of each test point were obtained. Secondly, the original engine bonnet materials were changed to AFS materials. The parameters of the new engine bonnet were preliminarily designed. Referring to head protection, the material parameter combinations were studied by using an orthogonal experimental design method. Finally, a weight analysis was carried out. The results indicated that the new bonnet could protect a pedestrian’s head effectively and also reduce the weight of the vehicle to improve fuel economy.